-2(t-5)=-6

Simple and best practice solution for -2(t-5)=-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(t-5)=-6 equation:


Simplifying
-2(t + -5) = -6

Reorder the terms:
-2(-5 + t) = -6
(-5 * -2 + t * -2) = -6
(10 + -2t) = -6

Solving
10 + -2t = -6

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-10' to each side of the equation.
10 + -10 + -2t = -6 + -10

Combine like terms: 10 + -10 = 0
0 + -2t = -6 + -10
-2t = -6 + -10

Combine like terms: -6 + -10 = -16
-2t = -16

Divide each side by '-2'.
t = 8

Simplifying
t = 8

See similar equations:

| 4x+4=-4+2x+22 | | y=0.14x+2.85 | | 14.1+e=16 | | v+-3=-10 | | 2x^3-5x^2-5x-1=0 | | 15/21=h/24 | | 2.44-w=1 | | 7k-5k=16 | | -6=(3x+7) | | 3+n=7 | | M+.57=.61 | | 7(x+9)-7=56 | | 6x^2-72x+162=0 | | .666x-5=7 | | 8b+6b-7b=7 | | 5x+9x=18 | | 4x-5x-5=6x+7.4-4x | | 8.8a+11=99 | | -4(9-5y)+3y=10 | | .66x^2-4=12 | | 20+0.15m=80 | | 3y+(-4x)=21 | | P-8=4.9 | | 6x^2-6x-72=0 | | -y+5y= | | 8-x-2(x-1)=4(x+3) | | -7=-5y+4(y+9)-7(7+3y) | | 3.46+d=4.10 | | -24(3)+4(3)= | | 2x^3-3x^2-36x=0 | | 817+3=-5 | | 5x^2-27xy+10y^2=0 |

Equations solver categories